Leveraging social media for stroke awareness: a cross-sectional study in a tertiary care hospital in Uttar Pradesh, India - Behari, Ritwiz; Khan, Adeeba; Siddiqui, Naved; Pandey, Sudhakar (International Journal Of Community Medicine And Public Health, 2025)
Background: Stroke is a leading cause of mortality and disability globally, with a high incidence in India, particularly among younger populations. Awareness of stroke symptoms and risk factors is crucial for timely intervention and improved health outcomes. Methods: A cross-sectional observational study was conducted involving total number of participants 250 only kindly change 300 to 250 who were relatives of patients attending an outpatient clinic in a tertiary care hospital. A structured questionnaire with 23 questions assessed participants’ knowledge of stroke symptoms, risk factors, and social media usage related to stroke awareness. Results: The study found that only 48% of participants could identify all warning signs of stroke, and just 30% knew to call an ambulance immediately upon suspicion of a stroke. Although 90% of participants were active on social media, only 10% had encountered stroke-related information online. Instagram was the most frequently used platform, yet 93% reported no exposure to relevant educational content. Notably, 55% believed social media could effectively raise awareness about stroke symptoms and responses. Conclusions: The findings highlight significant gaps in stroke awareness among participants, emphasizing the underutilization of social media in disseminating critical health information. Targeted social media campaigns could enhance public knowledge and improve response times during stroke incidents, potentially reducing the burden of stroke-related disabilities.